Analisis Kebutuhan dan Karakteristik Peserta Didik pada Pembelajaran IPA dalam Mendukung Pembelajaran Berdiferensiasi di Kurikulum Merdeka - Fatimah Fatimah; M. Rezeki Muamar (Jurnal Penelitian Pendidikan IPA, 2024)
The problem that occurs in the implementation of Kurikulum Merdeka is the limited of differentiated and integrated Computational Thinking (CT) teaching materials provided by the government which can be used by teachers to direct students to think computationally thinking while focus to students' learning needs, especially in science learning which is a developmental milestone of science development. The aims of the research are to analyze students’ needs and character mapping of students toward the development of differentiated digital modules integrated CT in science subject. The method used in this research is a qualitative descriptive method involving 10 junior high schools that have implemented Kurikulum Merdeka. The population in this study was 19,034 students of 101 junior high schools in Bireuen District. Meanwhile, the sample used in this research was 260 junior high school students from 10 schools in Bireuen District. From the results of data analysis, it was found that the proportion of learning styles for junior high school students in Bireuen District is dominated by auditory learning styles. Furthermore, the distribution of multiple intelligences is dominated by students with logical/mathematic intelligence. Lastly, the student perceives that science learning is enjoyable